2018
DOI: 10.1111/pin.12724
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ovarian cancer immunoreactive antigen domain containing 2 (OCIAD2) is associated with poor prognosis in lung adenocarcinoma

Abstract: The clinicopathological implications of ovarian cancer immunoreactive antigen domain containing 2 (OCIAD2) in lung adenocarcinoma were investigated. The expression of OCIAD2 in 191 surgically resected lung adenocarcinomas was examined using immunohistochemistry. OCIAD2 expression was quantified using the H‐score and dichotomized as high or low. High OCIAD2 protein expression was significantly correlated with vascular invasion (P = 0.0018), lymphatic permeation (P = 0.049), T factor (P = 0.0024), and pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Gremlin 1 (GREM1) protein, highly overexpressed in tumors (log2 FC > 5, FDR < 0.01) in our study, is a known marker of poor prognosis in lung cancer (Mulvihill et al, 2012) and implicated in EMT and metastasis processes (Figure S7D; Table S7) (Cleynen et al, 2007;Friedman et al, 2004;Tang et al, 2019). Ovarian cancer immunoreactive antigen domain containing 2 (OCIAD2), highly overexpressed in tumors (log2 FC > 4, FDR < 0.01), is a known poor prognosis marker (Sakashita et al, 2018), as are stress-related marker candidates DHFR, HYOU1, LDHA, and CBX8 (Fahrmann et al, 2016;Lladó et al, 2009;Takei et al, 2017). Significantly hyperphosphorylated and hyperacetylated sites are described in Table S7.…”
Section: Characterization Of Smoking-related Phenotype In Tumors and Natsmentioning
confidence: 57%
See 1 more Smart Citation
“…Gremlin 1 (GREM1) protein, highly overexpressed in tumors (log2 FC > 5, FDR < 0.01) in our study, is a known marker of poor prognosis in lung cancer (Mulvihill et al, 2012) and implicated in EMT and metastasis processes (Figure S7D; Table S7) (Cleynen et al, 2007;Friedman et al, 2004;Tang et al, 2019). Ovarian cancer immunoreactive antigen domain containing 2 (OCIAD2), highly overexpressed in tumors (log2 FC > 4, FDR < 0.01), is a known poor prognosis marker (Sakashita et al, 2018), as are stress-related marker candidates DHFR, HYOU1, LDHA, and CBX8 (Fahrmann et al, 2016;Lladó et al, 2009;Takei et al, 2017). Significantly hyperphosphorylated and hyperacetylated sites are described in Table S7.…”
Section: Characterization Of Smoking-related Phenotype In Tumors and Natsmentioning
confidence: 57%
“…Significantly hyperphosphorylated and hyperacetylated sites are described in Table S7. Although only a few among these marker candidates are currently targeted by therapeutics in clinical trials, their strong and consistent differential expression and associations with lung cancer biology and decreased survival support potential utility in early detection and prognostic stratification (Kim et al, 2018a;Mulvihill et al, 2012;Sakashita et al, 2018;Wang et al, 2015).…”
Section: Characterization Of Smoking-related Phenotype In Tumors and Natsmentioning
confidence: 99%
“…OCIAD2 was originally discovered as an immunoreactive antigen in patients with ovarian cancer (Luo et al, 2001). Later OCIAD2 was reported dysregulated in various types of cancer, however, its regulatory roles in cancer progression is still unclear and appears to be tumor type-dependent (Nagata et al, 2012;Wu et al, 2017;Sakashita et al, 2018). In addition OCIAD2 was also implicated in Alzheimer disease (Han et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…20 Although OCIAD2 was first correlated with favorable prognosis, 20 subsequent immunohistochemical analyses revealed it was an independent prognostic factor for lung adenocarcinoma. 21 Recently, Hong et al have shown that OCIAD2 is located at the mitochondria and controls mitochondria-initiated apoptosis. 22 Besides OCIAD2, Noguchi's group have also reported that Epithelial Cell Transforming 2 (ECT2) 23 and Immunoglobulin Binding Protein 1 (IGBP1) 24 have significantly higher expression in (early) invasive adenocarcinoma than in AIS (Figure 2).…”
Section: The Noguchi Classification and Molecular Mechanisms Of Lung Adenocarcinoma Progressionmentioning
confidence: 99%